Salicylaldehyde-based molecular sensor with one facile step toward visual detection of viscosity. Issue 1 (29th November 2022) - Xu, Lingfeng; Wang, Yuefeng; Jiang, Chuan; Huang, Yanrong; He, Genhe; Liu, Limin
Abstract : A salicylaldehyde-based molecular sensor was synthesized in a one-step facile way and designed for visual detection of viscosity in liquids. Abstract : Liquid safety has become one of the urgent affairs in global public health studies, and a noninvasive and effective viscosity inspection method is expected to ease the burden of continuously increasing health problems. In this study, one kind of activatable molecular sensor (DTPMP ) based on a salicylaldehyde derivate has been synthesized via the Schiff base condensation reaction. This sensor is comprised of a donor–acceptor conjugated structure. We proposed the viscosity of the liquid microenvironment as a marker, and a rotatable conjugate structure was utilized as the recognition site. The molecular sensor was synthesized in a one-step facile way, and DTPMP displayed a longer emission wavelength and larger Stokes shift (142.5 nm in water, 116.8 nm in glycerol), which endows the sensor with the capacity of avoiding auto-fluorescence and achieving high signal-to-noise ratio imaging. The rotation of aromatic rings in DTPMP is restricted in a high-viscosity microenvironment, with the gradually increasing fluorescence emission signal at 532 nm. Moreover, the DTPMP sensor exhibits high adaptability, selectivity, sensitivity, and good photostability in various commercial liquids. Significantly, this sensor has successfully been applied not only in the determination of the thickening effects of food gum but also in the detection of viscosity enhancement during the liquid food spoilage process, which may be helpful in screening the metamorphic stage. We expected that this unique strategy will reinvigorate the continued perfection of the fluorescence technique toward liquid safety investigation.